2013
DOI: 10.1371/journal.pone.0073697
|View full text |Cite
|
Sign up to set email alerts
|

High “Normal” Blood Glucose Is Associated with Decreased Brain Volume and Cognitive Performance in the 60s: The PATH through Life Study

Abstract: ContextType 2 diabetes is associated with cerebral atrophy, cognitive impairment and dementia. We recently showed higher glucose levels in the normal range not to be free of adverse effects and to be associated with greater hippocampal and amygdalar atrophy in older community-dwelling individuals free of diabetes.ObjectiveThis study aimed to determine whether blood glucose levels in the normal range (<6.1 mmol/L) were associated with cerebral volumes in structures other than the hippocampus and amygdale, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
3
37
2
1
Order By: Relevance
“…However, several studies have suggested that higher glucose levels may contribute to cognitive deficits or decline among those without diabetes,4 6 10 a finding we could not confirm. Methodological variations may be at play.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, several studies have suggested that higher glucose levels may contribute to cognitive deficits or decline among those without diabetes,4 6 10 a finding we could not confirm. Methodological variations may be at play.…”
Section: Discussioncontrasting
confidence: 73%
“…High glucose levels among individuals with type 2 diabetes have been linked to poorer global cognition, verbal memory, and executive function2 and declines in global cognition and processing speed 3. Furthermore, elevated but clinically normal glucose levels have been linked to cognitive status in studies including individuals without diabetes4 10 and in studies that did not use diabetes classification 11 12. Among individuals without diabetes, it appears that this effect may be stronger in women than men, specifically in relation to memory performance 5 6…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this phenomenon revealed that hyperglycemia might cause an increasing risk of microvascular disease and structural changes in the hippocampus [30]. Besides, Morby [31] pointed out that even among the elderly population with higher-blood glucose levels in the normal range, the frontal cortex could be impacted to result in impairment in working memory, executive function, information processing speed and language. Another research focusing on the relationship between MCI and diabetes suggested an association of MCI with diabetes mellitus in the aspects of onset, duration and severity [32].…”
Section: Comparison Of Cognitive Function Of T2dm Patients With Diffementioning
confidence: 99%
“…One study has even suggested that elderly people with relative high blood glucose level in normal range also suffer from cognitive impairment (Mortby et al 2013). Moreover, some studies have reported possible therapeutic effect of hypoglycemic measures on cognitive impairment (Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications Study Research Group et al 2007;Luchsinger et al 2011), and repeated hypoglycemic episodes caused by inappropriate treatment may still cause the progression of dementia (Whitmer et al 2009).…”
Section: Introductionmentioning
confidence: 99%